The tail pigmentation pattern of C57BL/6J mice affects nociception/pain quantification in the tail flick test - Wen, Ting (2008)
The heat radiant tail flick test is commonly used to quantify nociception and pain levels. Likewise, the C57BL/6J strain of mice is frequently used in pain-related studies as transgenic mice are often backcrossed onto this background. C57BL/6J mice naturally develop non-pigmented patches of variable length on the distal part of the tail that could conceivably modify the response latency in tail flick assays. Here we find that these non-pigmented regions, in a position-independent manner, significantly increase the response latency in the heat radiant tail flick assay, but not the warm water immersion test. This finding demonstrates that the extent of pigmentation, and not other potential variables between pigmented and non-pigmented skin, affects radiant heat tail-flick latency, and should be considered in the design of pain-related studies using mice with variable tail pigmentation.